Impact of physical activity on symptoms of depression and anxiety in adolescents during the COVID-19 pandemic - Yang, Hai-Ying; Sun, Li-Hong (Frontiers in Psychiatry, 2025)
BackgroundAdolescents faced increased psychological distress during the COVID-19 pandemic. While prior research suggests physical activity (PA) may mitigate depression and anxiety, findings have been inconsistent and rarely focus on adolescents during prolonged lockdowns. This study addresses this gap by evaluating the association between daily PA duration and mental health outcomes among Chinese adolescents during the pandemic.MethodsA cross-sectional online survey was conducted from June 1–30, 2020, among 1,142 adolescents aged 11–18 years in Pidu District, Chengdu City, China. Depressive and anxiety symptoms were assessed using the Center for Epidemiological Studies Depression Scale for Children (CES-DC) and the Generalized Anxiety Disorder 7-item scale (GAD-7), respectively. PA was self-reported and categorized as <30, 30–60, and >60 minutes/day. Logistic regression was used to estimate odds ratios (ORs) for depression (CES-DC >15) and anxiety (GAD-7 ≥5), using ≥30 min/day as the reference.ResultsDepressive symptoms were reported by 40.7% of participants and anxiety symptoms by 24.1%. Compared to adolescents with ≥30 min/day of PA, those with <30 min/day had significantly higher odds of depression (OR = 1.722, 95% CI: 1.342–2.226) and anxiety (OR = 1.653, 95% CI: 1.299–2.521). Additional independent predictors included female sex, sleep duration <6 hours, and self-reported decline in learning efficiency.ConclusionsInsufficient PA (<30 min/day) was independently associated with elevated depression and anxiety symptoms in adolescents during the pandemic. These findings support promoting ≥30 minutes of daily PA as a scalable, non-pharmacological strategy to protect adolescent mental health during public health emergencies.